Overcoming Security Challenges in Digital Government in West Papua - Ayu Sita Maharani (Asian Digital Governance Problems, 2024)
Purpose: This research aims to identify and analyze the security challenges faced by digital government initiatives in West Papua, Indonesia Subjects and Methods: The study employs a quantitative method, conducting surveys among government employees involved in digital transformation projects. Results: The results of the analysis indicate that there is still a low level of awareness and understanding of digital security among government employees in West Papua. These findings highlight the importance of increasing awareness and training on digital security for government employees involved in digital government initiatives. Conclusions: The conclusion of this research is the highlight several key findings regarding cybersecurity in digital governance in West Papua. There is a significant need for increased cybersecurity awareness and education, as well as greater investment in cybersecurity infrastructure and resources.